2019
DOI: 10.1155/2019/5934274
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Modeling of 3D Flow Field among a Compound Stilling Basin

Abstract: Due to great velocity gradients among the outgoing flow, it is much common to form large-scale reverse flow with oblique movements outside the conventional separated stilling basin. Aimed at above problems, this paper proposes to remove the longitudinal splitter wall and then physically and numerically investigate the corresponding influence upon the compound stilling basin. The standard k-ε, renormalization group k-ε, realizable k-ε, and large eddy simulation turbulence models are all employed to reveal downs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Such thresholds of k and τ xz can be applied to identify field conditions with the potential to reduce successful hatching of eggs in natural streams, and evaluate whether natural or anthropogenic features could cause mortality where survival of eggs is desirable. For example, turbulent kinetic energy can be high below dams where k can exceed 2.0 m 2 s −2 throughout the water column and persist for relatively large distances downstream of the structure (100 m) (Zhou and Wang 2019). Odeh et al (2002) listed previous reports that documented magnitudes of common shear stresses (in N m −2 ) associated with average flows in natural streams (see Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Such thresholds of k and τ xz can be applied to identify field conditions with the potential to reduce successful hatching of eggs in natural streams, and evaluate whether natural or anthropogenic features could cause mortality where survival of eggs is desirable. For example, turbulent kinetic energy can be high below dams where k can exceed 2.0 m 2 s −2 throughout the water column and persist for relatively large distances downstream of the structure (100 m) (Zhou and Wang 2019). Odeh et al (2002) listed previous reports that documented magnitudes of common shear stresses (in N m −2 ) associated with average flows in natural streams (see Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…For both upstream and downstream parts, a coarse mesh in the flow direction was used to reduce the number of cells and computing time [ 29 ]. Ten boundary layers contracting with a ratio of 1.1 were placed at the bottom wall of the stilling basin, and the grid point of the first layer was placed in the log law region ( ) [ 17 ]. A constant average velocity was used at the upstream inlet boundary for the water phase.…”
Section: Numerical Simulationsmentioning
confidence: 99%
“…The fine grid convergence index (GCI) as suggested by Celik et al [ 16 ] was used in their study to perform a mesh sensitivity analysis. Zhou and Wang [ 17 ] simulated the 3D flow field among a compound stilling basin using the commercial CFD package FLOW-3D. The simulation results of four turbulence models (standard k- ε , RNG k- ε , realizable k- ε , and large eddy simulation turbulence models) were compared, and the RNG k- ε turbulence model showed the most successful agreement with the experimental results.…”
Section: Introductionmentioning
confidence: 99%
“…A study of a free surface three-dimensional CFD model to the tailrace of The Dalles Project was found to be in good agreement with physical models [4]. The comparative study between RNG and standard k-ε turbulence models concluded that the RNG model was found to perform better near the bed regions in submerged hydraulic jumps [5] and in compound stilling basins [6]. The characteristics of the hydraulic jump in a stilling basin of multihorizontal submerged jets were studied by using VOF RNG k-ε and Mixture RNG k-ε turbulence models, and the numerical simulation results such as water depth, velocity profile and pressure distribution were verified by a series of model experiments [7].…”
Section: Introductionmentioning
confidence: 99%